PENGARUH EKSTRAK ETANOL DAUN JAMBU AIR (SYZYGIUM AQUEUM) TERHADAP BAKTERI ISOLAT KLINIS - Titi Hariyati; Dwi Soelistya Dyah Jekti; Yayuk Andayani (Jurnal Penelitian Pendidikan IPA, 2015)
Syzygium aqueum plant of the family Myrtaceae is native of Malaysia and Indonesia and is known as the water rose. The active compound is useful as an antibacterial. This study aimed to determine the effects of ethanol extracts of guava leaves (S. aqueum) as an antimicrobial against clinical isolates bacteria in vitro. The design used in experiment was a Completely Randomized Design (CRD). Data were analyzed using the Kruskal-Wallis test. Results of statistical analysis using SPSS 20 for windows indicated that the ethanol extract of guava leaves has a significant (P<0,05) effect in inhibiting the growth of clinical isolates bacteria. MIC (Minimum Inhibition Concentration) of ethanol extracts for each bacterium can not be determined because the guava leaf extract was very dark. The MBC (Minimum Bacterisidal Concentration) of ethanol extract of guava leaf  for both S. aureus and S. dysenteriae was 20%.  The MBC of the extract for E. coli, S. thypi, V. cholerae was 25%, where as for B. cereus was at concentration of 50%. It can be concluded that guava leaf has highly potential as a source of antimicrobial agent.Keywords:Antibacteria, Guava Leaf, Clinical Isolates Bacteria, Ethanol Extract